(untitled) (Universal International Scientific Journal, 2026)
This article considers the concept of lacuna (in linguistics, “gap”) as a linguistic unit and analyzes its interpretation in different languages. Lacuna is a unit that represents semantic, pragmatic or culturological components that exist in a particular language or culture, but do not have a complete equivalent in other languages or cultures. The article considers the classification of lacuna (lexical, grammatical, pragmatic, culturological and stylistic lacunas), methods of identification (contrast analysis, corpus research, translation practice), and intra- and interlingual manifestations of lacuna